2005
DOI: 10.1243/030932405x30812
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Strain Gauge Thermal Effects During Residual Stress Hole Drilling Measurements

Abstract: The hole drilling residual stress measuring method is based on drilling a small hole in a material sample and measuring the strain relieved in the hole vicinity by a special strain gauge rosette. The temperature and thermal strain induced by the drilling process can cause significant errors in the relieved strain measurement. The paper deals with computer simulation of the thermomechanical process in the sample during drilling. The first part is devoted to the evaluation of heat flux from the drilling tool to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Successively, by using the same calculation code, the uncertainty of the computed RS as well as the single uncertainty contribution related to each influence parameter, have been computed by considering the following typical uncertainty mean values of the main influence parameters (taken from literature [1–18, 21–23]):…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Successively, by using the same calculation code, the uncertainty of the computed RS as well as the single uncertainty contribution related to each influence parameter, have been computed by considering the following typical uncertainty mean values of the main influence parameters (taken from literature [1–18, 21–23]):…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…In the following, a procedure to correct the main errors affecting the computed RS, is proposed. It considers all the error sources described in the previous chapter, and it is based on the above mentioned studies reported in literature [2][3][4][5][6][7][8][9][10][11].…”
Section: Procedures For the Correction Of The Main Errors Affecting Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Zubin [15] carried out a theoretical error investigation of calibration beams used for the determination of the gage factor. In 2005, a computer simulation of strain gage thermal effect errors during residual stress hole drilling measurements was carried out and is presented in reference [16]. In 2006, Robinson discussed the fact that stress analysis engineers are probably no more aware of the background regarding some aspects of the gages than is the average person [17].…”
Section: Introductionmentioning
confidence: 99%